2018
DOI: 10.1016/j.surg.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Risk-stratified clinical pathways decrease the duration of hospitalization and costs of perioperative care after pancreatectomy

Abstract: Implementation of risk-stratified pancreatectomy clinical pathways decreased median stay and cost of index hospitalization after pancreatectomy without unfavorably affecting rates of perioperative adverse events or readmission, or discharge disposition. Outcomes were most favorably improved for low-risk pancreatoduodenectomy and distal pancreatectomy. Additional work is necessary to decrease the rate of postoperative pancreatic fistula, minimize variability, and improve outcomes after high-risk pancreatoduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…As such, a potential starting point for improving perioperative care in CRS/HIPEC may include implementation of risk‐stratified clinical pathways. For example, Denbo et al 11 reported on outcomes from risk‐stratified postpancreatectomy pathways. The authors developed unique pathways for the following: low‐risk pancreaticoduodenectomy (PD), high‐risk PD, and distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a potential starting point for improving perioperative care in CRS/HIPEC may include implementation of risk‐stratified clinical pathways. For example, Denbo et al 11 reported on outcomes from risk‐stratified postpancreatectomy pathways. The authors developed unique pathways for the following: low‐risk pancreaticoduodenectomy (PD), high‐risk PD, and distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nasogastric tube removal was removed at different postoperative days for low‐risk PD (2), high‐risk PD (3), and distal pancreatectomy (0). Their results demonstrated a decrease in median hospital stay after pancreatectomy from 10 to 6 days, as well as a decrease in median cost of index hospitalization by 22% after pathway implementation 11 . Second, development of consensus perioperative guidelines and multi‐institutional collaborative efforts to improve adherence to these guidelines, particularly among high‐volume institutions, would be potentially beneficial for improving care and providing clinical management guidance for lower‐volume institutions as well.…”
Section: Discussionmentioning
confidence: 99%
“…A periadventitial dissection of the right lateral aspect of the SMA is conducted from the level of the first jejunal branch of the superior mesenteric vein to the takeoff of the SMA from the aorta 64,65 . Postoperatively, patients are assigned to care pathways based on their calculated risk of pancreatic fistula 66 . Upon recovery from surgery and review of final pathology, a multidisciplinary team informs the delivery of postoperative systemic chemotherapy 67 …”
Section: General Treatment Strategy At MD Andersonmentioning
confidence: 99%
“…We suggest a 3-pronged approach in the efforts towards improving the compliance rates to ERAS® or clinical pathways: Patient Prehabilitation, Periodic Provider (Treating team) education and training, and Progressive Refinement of the Clinical Pathways. Refinement measues may include devising Personlized or Risk-Stratified Clinical Pathways (74,143), with the "risk" being estimated based on factors such as peroperative BMI, co-morbidities or likelihood of post-operative pancreatic fistula, as well as addition of complimentary elements to the pathways like "Perioperative Surgical Home" (PSH) (144) and/or tele-discharge program (145) with "virtual" visits in the post-operative period would make ERAS® safer, leading to increased acceptance and sustained improvements in patient care. From a clinician's or policymaker's perspective, we certainly need to dissect out the economic implications of ERAS protocols, as concrete proof of financial gains in terms of grossly positive projected return on investment (108), in addition to clinical benefits would provide an additional (though not the main) incentive for implementation of ERAS®.…”
Section: Future Directionsmentioning
confidence: 99%